Leaching of immobilized cesium from NaOH-activated fly ash-based geopolymers. (October 2022) - Jain, Shubham; Banthia, Nemkumar; Troczynski, Tom
Abstract: This study investigated the effects of cesium (Cs) dosage (2–20 wt.%) and curing time (7–180 days) on the leaching behavior and immobilization of Cs in NaOH-activated fly ash-based geopolymers (FA-GP). The Cs leaching behavior and leachability index ( LX ) were evaluated per ANS-16.1. FA-GP were characterized using XRD and N2 adsorption-desorption isotherms. The results revealed that Cs dosage affects the resulting phases and pore structure of FA-GP and influences the Cs immobilization. The higher Cs dosage (≥8 wt.%) provides conditions for in-situ pollucite crystallization within the FA-GP matrix (cured at 90 °C for 7 days) and significantly enhances Cs immobilization ( LX values from 11.5 to 14.5). Cs leaching resistance of FA-GP cured at 22 °C improved with curing time. Diffusion was determined to be the primary leaching mechanism. The results advocate the use of FA-GP as an effective immobilization material, mainly containing a high concentration of Cs. Graphical abstract: Image 1 Highlights: Cesium dosage and curing time affected cesium immobilization in fly ash geopolymers. High cesium dosage (≥8 wt.%) aided formation of in-situ pollucite in geopolymers. Leaching resistance of geopolymers cured at 22 °C improved with curing time. Diffusion was determined to be the primary leaching mechanism.